Please, Mind the Gap. Gender and Computer Science Education - Kwaśnik, Marta; Karwowski, Maciej (Wydawnictwo Naukowe UAM, 2015)
Functioning in contemporary reality requires a variety of different skills, but computer skills are among the most prevalent ones. In this article, we review theories and research related to the gender gap in computing and computer science education, as well as provide several possible lines of explanation of this gap, organized around the psychobiosocial model of gender differences. We demonstrate this gap in Poland using different data-based exemplifications, i.e., showing the gender gap among participants of national contests in programming, awardees of prestigious fellowships for young scientists or showing gender differences in scholarly positions. We discuss reasons and consequences of the identified gap in education, but also in society as a whole.
Keywords: computing; computer science; gender gap; biosocial model